(untitled) (CIPEEX, 2026)
Introduction: Cone beam computed tomography (CBCT) stands out in dentistry due to its ability to generate highly accurate three-dimensional images. Combined with 3D printing, this technology enables advances in guided endodontics, especially for the precise execution of complex endodontic accesses. However, the impact of different CBCT scanners and specific image acquisition protocols on the accuracy of 3D-printed surgical guides remains underexplored. Objective: This study aims to evaluate in detail the influence of the type of CT scanner and the protocol used in image acquisition on the dimensional and angular accuracy of prototype guides used for endodontic accesses. Method: Samples of extracted bovine teeth will be used, appropriately selected, prepared, and fixed in acrylic resin blocks. Tomographic images will be acquired using four different CBCT scanners, each employing their respective standard protocols. The initial images obtained will be integrated with the intraoral scans of the specimens, allowing digital planning of the guides, followed by printing in light-cured resin. After the guided accesses are performed, new tomographic scans will be performed and superimposed on the initial images to quantitatively assess the accuracy of the procedures performed in relation to the initial digital planning. Expected Results: The results of this study are expected to provide scientific data that directly contribute to optimizing the use of digital technology in Endodontics, improving clinical safety, reducing operative errors, and increasing treatment predictability.